ANALISIS RASIO RENTABILITAS DALAM MENILAI KINERJA KEUANGAN PERUSAHAAN PT. BUMI RESOURCES TBK. TAHUN 2024-2025 - Adelia Septiani Putri (Ekonomi Syariah STAI Sangatta Kutai Timur, 2026)
This study aims to analyze the financial performance of PT Bumi Resources Tbk for the 2024–2025 period based on profitability ratios. The ratios used in this study include Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The research employed a quantitative approach with a descriptive method. The data used were secondary data obtained from the financial statements of PT Bumi Resources Tbk for the years 2024 and 2025. Data analysis was conducted by calculating and comparing the profitability ratios for both periods. The results indicate that Net Profit Margin (NPM) increased from 6.63% in 2024 to 8.58% in 2025. Return on Assets (ROA) increased from 2.16% to 2.90%, while Return on Equity (ROE) increased from 3.15% to 4.24%. The increase in these three ratios indicates that PT Bumi Resources Tbk experienced an improvement in financial performance, reflected in the company's enhanced ability to generate profits through sales, asset utilization, and equity management. Therefore, the financial performance of PT Bumi Resources Tbk during the 2024–2025 period can be considered to have shown positive growth.